Serum biochemical parameters and cytokine profiles associated with natural African trypanosome infections in cattle - Bakari, S.M.; Ofori, J.A.; Kusi, K.A.; Aning, G.K.; Awandare, G.A.; Carrington, M.; Gwira, T.M. (Parasites and Vectors, 2017)
Background: Animal African trypanosomiasis (AAT) greatly affects livestock production in sub-Saharan Africa. In Ghana prevalence of AAT is estimated to range between 5 and 50%. Studies have reported serum biochemical aberrations and variability in cytokine profiles in animals during infection. However, information regarding the biochemical parameters and cytokine profiles associated with natural infections are limited. This study was therefore aimed at investigating changes in the levels of serum biochemical parameters and inflammatory cytokines during a natural infection. Methods: Nested internal transcribed spacer (ITS)-based PCR and sequencing were used to characterise trypanosome infection in cattle at two areas in Ghana (Adidome and Accra) of different endemicities. The cattle were sampled at four to five-week intervals over a period of six months. Levels of serum biochemical parameters, including creatinine, cholesterol, alkaline phosphatase (ALP), alanine aminotransferase (ALT), total bilirubin and total protein and cytokines (interleukin 10, interleukin 4, interleukin 12, interferon gamma and tumor necrosis factor alpha) were measured in serum samples and then compared between infected cattle and uninfected controls. Results: The predominant trypanosome species detected in Accra (non-endemic) and Adidome (endemic) were Trypanosoma theileri and Trypanosoma vivax, respectively. Serum biochemical parameters were similar between infected and uninfected cattle in Accra. Infected cattle at Adidome however, had significantly higher levels of ALP, creatinine, total protein and total bilirubin (P < 0.05) and significantly lower levels of cholesterol (P < 0.05) at specific time points. At basal levels and during infection, significantly higher pro-inflammatory to anti-inflammatory (Th1/Th2) cytokine ratios were observed in cattle at Adidome compared to Accra (P < 0.05), indicating a shift towards Th1 immune response in Adidome. Levels of IL-10 were, however, significantly elevated in infected cattle in Accra (P < 0.05), suggesting high anti-inflammatory cytokine response in Accra. Conclusion: These results suggests that cattle in an endemic area repeatedly infected with trypanosomes of different species or different antigenic types demonstrate high pro-inflammatory (Th1) immune response and biochemical alterations whereas cattle in a non-endemic area with predominantly chronic T. theileri infections demonstrate high anti-inflammatory response and no biochemical alterations. © 2017 The Author(s).
Keywords: Animal African trypanosomiasis; Cytokine profiles; Natural infections; Serum biochemical parameters